If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -2 * 6 + 7 = 0 Multiply -2 * 6 12 + -12 + 7 = 0 Combine like terms: 12 + -12 = 0 0 + 7 = 0 7 = 0 Solving 7 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2xy+xy-y=0 | | .8t-.3t=6.5 | | 3x^2-9x+38=2x^2+18 | | (1/6x)-(1/3)=(-2/3x)-(1/3) | | 4=40t-5t^2 | | 4x-3+3x+2= | | 2+4*5-3(25)= | | 8y/2=968 | | 12x-24=y | | 10x+5+4x-7=180 | | -50x^6-5x^5= | | 3x+8z=2+2y | | 4x-7=65 | | 10x+5+4x-7=65 | | (4x-7)(2x-1)=0 | | 3x-2+2x+6+4x-4=180 | | 12d+4=7-d | | 3x-2+2x+6=180 | | -13+2x=x+13 | | 9x+6+10x-1+10x+7=180 | | 10x-1+10x+7=180 | | 1/4=8 | | log(2)x=2 | | -81+9x=179-11x | | -4+(-10)-(-3)-12= | | -44-4x=-12x+52 | | 7-3=-1 | | 21x+50-16x=10 | | 10x+5y+2z+k=100 | | -3/4*-4/9 | | -3/4*-4/8 | | 7x-45=5x-5 |